2018
DOI: 10.1519/jsc.0000000000002551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Physical Workload by Position During Match in Elite Bandy

Abstract: Blomqvist, S, Ervasti, PE, and Elcadi, GH. Evaluating physical workload by position during match in elite bandy. J Strength Cond Res 32(9): 2616-2622, 2018-To improve current understandings of physical workload (WL) in elite bandy, 10 bandy players were monitored for heart rate (HR) during 13 matches over 1 championship season. Participants were divided into 5 subgroups according to playing position-libero, defender, halves, midfielder, and forward. Heart rate measurements were analyzed with 2 different method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…In this present study, a visual analysis of all figures indicates that halves, midfielder, and forward had the highest overall demands for the variables total distance, mean velocity, and time spent in highest velocity zones. An explanation of the differences between this present study and Blomqvist et al (2018) may be due to the demands in acceleration and deceleration. In soccer, for example, it has been demonstrated that a high acceleration and repeated sprint ability are important factors of performance (Hoff & Helgerud, 2004;Mohr et al, 2003).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In this present study, a visual analysis of all figures indicates that halves, midfielder, and forward had the highest overall demands for the variables total distance, mean velocity, and time spent in highest velocity zones. An explanation of the differences between this present study and Blomqvist et al (2018) may be due to the demands in acceleration and deceleration. In soccer, for example, it has been demonstrated that a high acceleration and repeated sprint ability are important factors of performance (Hoff & Helgerud, 2004;Mohr et al, 2003).…”
Section: Discussioncontrasting
confidence: 83%
“…Bandy is a fast winter sport with maximum velocities up to 37 km/h and is categorized with intermittent movements' patterns. Additionally, it has been demonstrated that offensive positions spend more time (midfielder about 28 min and forwards 21 min) above lactate threshold vs defensive positions (libero 0.8 min, defender, and half about 15 min (Blomqvist et al, 2018). To skate in highvelocity zones the player´s anaerobic capacity can be an important key performance indicator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bandy is a winter team sport played on ice with similarities to soccer. Previous studies have investigated the physical workload during elite bandy by measuring heart rate and velocity patterns during match-play [1,2]. Blomqvist et al [1] observed that elite bandy players reach a heart rate between 70-90% of their maximum and spend up to 27% of the time above the lactate threshold during match-play depending on the player's position.…”
Section: Introductionmentioning
confidence: 99%